Figurative Language in Song Lyrics of The Album “The Record” By Boygenius - I Made Rasmawan; Yana Qomariana; PutuWeddha Savitri (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to identify and analyze the types of figurative language found in the song lyrics of Boygenius’s album “The Record.” The research specifically seeks to determine the various figurative language devices present in selected tracks and to interpret the meanings behind these expressions using Leech’s theory of meaning. By focusing on figurative language, the study aims to enhance the understanding of how artistic language in indie music conveys complex emotions and themes, enriching both literary appreciation and linguistic analysis. The data source for this research consists of the lyrics from four selected songs: “Emily I’m Sorry,” “True Blue,” “Cool About It,” and “Not Strong Enough” from Boygenius’s album “The Record.” Data collection was conducted through an observation and note-taking technique: the researcher listened to the songs on Spotify and obtained the lyrics from www.genius.com. The method of analysis employed a descriptive qualitative approach, with the researcher identifying and categorizing instances of figurative language in the lyrics. The study was guided by the framework of Knickerbocker and Reninger for figurative language types and Leech’s theory for interpreting the meanings, which include conceptual, connotative, social, affective, reflected, collocative, and thematic meanings. The study's results revealed a total of 36 instances of figurative language across the selected songs, encompassing similes, metaphors, personification, synecdoche, metonymy, hyperbole, irony, and paradox. Of these, 36 examples were analyzed in detail to explore their meanings. The findings demonstrate that Boygenius’s lyrics utilize a diverse range of figurative language,